1999
DOI: 10.1002/(sici)1097-0142(19990801)86:3<421::aid-cncr10>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Italian Cooperative Study for the treatment of children and young adults with localized Ewing sarcoma of bone

Abstract: BACKGROUND In 1991, the Italian Association for Pediatric Hematology‐Oncology and the National Council of Research (CNR) initiated an Italian Cooperative Study (SE 91‐CNR Protocol) with the main objective of improving the overall survival (SUR) and the event free survival (EFS) of children and young adults with localized Ewing sarcoma and primitive neuroectodermal tumors of bone compared with a previous study (IOR/Ew2 Protocol). METHODS Between November 1991 and November 1997, 165 patients were enrolled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
3
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 17 publications
7
90
3
5
Order By: Relevance
“…This result was comparable to the reports from other major series in ESFT of bone among Euro-American populations. 6,8,9,[23][24][25][26][27] Compared with the international variation in incidence, there was no considerable difference in the ratio of men to women, age distribution, or site distribution between Japanese patients and EuroAmerican patients (Table 2). Parkin et al also noted that there was no suggestion of any geographic or ethnic difference in the site distribution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result was comparable to the reports from other major series in ESFT of bone among Euro-American populations. 6,8,9,[23][24][25][26][27] Compared with the international variation in incidence, there was no considerable difference in the ratio of men to women, age distribution, or site distribution between Japanese patients and EuroAmerican patients (Table 2). Parkin et al also noted that there was no suggestion of any geographic or ethnic difference in the site distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] It has been well confirmed that ESFT patients with larger tumors have a poorer outcome. 6,17,27,29,30 However, recent studies have demonstrated that this classic prognostic factor may become less critical when it is accompanied by the application of more aggressive treatment, such as EW-92, 25 SE 91-CNR, 9 and P6 8 (see Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patients' ages were concentrated between four and 30 years. Age is a prognostic factor in the literature (16,17) , and this was observed in our sample, with lower five-year survival among patients over the age of 12 years (50.2%), compared with patients under the age of 12 years (71.7%) (P = 0.075). The mean age of the patients with pulmonary metastasis was slightly lower than the mean age among patients with extrapulmonary metastasis (respectively, P = 0.501 and P = 0.261), thus contrasting with local recurrence, which occurred in slightly older patients (P = 0.592).…”
Section: Discussionmentioning
confidence: 99%